Respuesta :

Answer:

  • The 67th term in the sequence is 268.

Step-by-step explanation:

We will use the formula 4(x), where x is the number of terms.

In this question, it says to find the 67th term. Let's substitute 67 into the formula to obtain our answer.

  • 4(x)
  • => 4(67)
  • => 268

Hence, the 67th term in the sequence is 268.

Hoped this helped.

[tex]BrainiacUser1357[/tex]

Ankit

Answer : 268

Step by step explanation:

Given sequence = 4,8,12,16...., (t1,t2,t3,t4,......)

first term(a) = 4

Common difference(d) = t2-t1 = 8-4 = 4

nth term of arhmetic sequence is given by,

tn = a+(n-1)d

To calculate the 67th term(t67) of sequence substitute n = 67,a = 4,d = 4 in above formula,

t67= 4+ (67-1)×(4)

t67 = 4+ 66×4

t67 = 4+264

t67 = 268

The 67th term of sequence is 268

Thanks for joining brainly community.

ACCESS MORE